Оцінка впливу використання фреймворку gRPC на продуктивність сервісу у порівнянні з REST API - Лисяков, М. С. (ХНУРЕ, 2023)
The increasing use of cloud computing has led to the widespread adoption of microservices as an architectural pattern. This approach involves breaking down large applications into smaller, independent packages that can be distributed across different environments, with the goal of achieving a cloud-native architecture. However, selecting the most effective communication mechanism between these services can be a complex task. To address this challenge, this thesis presents experimental findings comparing common inter-process communication methods, with a particular focus on REST APIs and Google gRPC.